Ormosia neillii (Fabaceae), a remarkable new tree species from the Cordillera del Cóndor plateaus in Ecuador - Juan Ernesto Guevara-Andino; John L. Clark; Daniel Navas-Muñoz (PhytoKeys)
A new species, Ormosia neillii (Fabaceae), is described and illustrated from the tepui-like formations of the Cordillera del Cóndor Region in south-eastern Ecuador. Morphological similarities with other species of Ormosia are examined and discussed. Based on IUCN guidelines, a preliminary conservation status of Endangered (EN) is recommended.